A review to the pedagogical reading and writing practices in French language teaching in official and private institutions of Bogotá (Papeles, 2017)
This article reflects on the pedagogical practices of reading and writing in relation to the current situation of teaching French in official and private schools in Bogotá, Colombia. From this perspective, an overview is presented on these pedagogical practicesto go into how teachers are promoting the development of competences linked to the two skills mentioned. The text proposes the incorporation of new and diverse methods, mediations and learning strategies, taking into account the learners, both individual and collective interests, institutional modalities, among other factors thatinfluence the teaching of French. This is how the teacher assumes the role of guide and facilitator in the promotion of experiences that generate in the student a genuine interest in learning the foreign language.
Keywords: reading; writing; methods; mediations; learning strategies